A systematic look at structural diversity of metal phosphonates - Bulut, Aysun; Dogan, Nurcan; Kirpi, Erdogan; Zorlu, Yunus; Yucesan, Guendog (WILEY-V C H VERLAG GMBH, 2024)
Herein, we report the synthesis of three new copper phosphonate frameworks using a tetrahedral-shaped organic building block, methane tetra-p-phenylphosphonic acid (H8-MTPPA), and three different N-ancillary ligands terpyridine (terpy), 2,2'-bipyridine (2,2'-bpy), phenanthroline (phen) to optimize the ligand binding modes on copper coordination sphere to generate molecular secondary building units (SBUs) in metal organophosphonates. We report the crystal structures of rod-shaped one-dimensional zig-zag chain structure, [{Cu(terpy)}(H6-MTPPA)(H2O)]& sdot;2H2O, three-dimensional framework, [{Cu5(2,2'-bpy)2}(H2-MTPPA)(H4-MTPPA)], and one-dimensional structure [{Cu2(phen)2}(H4-MTPPA)]& sdot;4H2O. Magnetic analysis of three-dimensional copper phosphonate framework, namely [{Cu5(2,2'-bpy)2}(H2-MTPPA)(H4-MTPPA)], showed paramagnetic behavior. Crystal structures were characterized by single crystal X-ray diffraction, FT-IR, and thermogravimetric analysis (TGA). Three novel metal-phosphonate frameworks, namely, rod-shaped one-dimensional [{Cu(terpy)}(H6-MTPPA)(H2O)]& sdot;2H2O, three-dimensional [{Cu5(2,2'-bpy)2}(H2-MTPPA)(H4-MTPPA)] and one-dimensional [{Cu2(phen)2)}(H4-MTPPA)]& sdot;4H2O, constructed from tetrahedral shaped methane-p-tetraphenylphosphonic acid (MTPPA) and N-ancillary organoimine ligands were synthesized and characterized by X-ray crystallography. Magnetic analysis of [{Cu5(2,2'-bpy)2)}(H2-MTPPA)(H4-MTPPA)] exhibited paramagnetic behavior.image
Keywords: MOF; Organophosphonates; Magnetic properties; Copper phosphonates; Coordination modes; FRAMEWORKS; Chemistry